A Micro-Intervention Model Based on Behavior Change for Addressing Littering Behavior - Elisabeth Endang Prakosawati; Djoko Widagdo (Lembaga Bale Literasi, 2026)
This study aims to examine and synthesize the literature on A Micro Intervention Model Based on Behavior Change for Addressing Littering Behavior, with particular attention to the behavioral determinants of littering, the forms of micro intervention applied in previous studies, and their theoretical and practical implications for littering prevention. The study employed a Systematic Literature Review following the PRISMA framework to ensure a structured, transparent, and traceable review process. The literature was identified through database searching using behavior change and littering related keywords, with the review limited to journal articles published between 2022 and 2026. The PRISMA based selection process began with 314 records, which were subsequently screened through title and abstract review, followed by full text eligibility assessment using predefined inclusion and exclusion criteria, resulting in 15 studies being included in the final synthesis. The review shows that littering behavior is consistently shaped by the interaction of attitudes, social norms, perceived behavioral control, situational cues, and environmental support. The findings also indicate that general awareness, infrastructure provision, or regulation alone are insufficient to produce stable anti littering behavior. More effective outcomes are associated with micro interventions that are concrete, context sensitive, and directed at specific behavioral mechanisms, especially those related to norms, implementation processes, and routine decision making. The review further confirms the persistence of an intention behavior gap, suggesting that positive attitudes or intentions do not automatically lead to consistent anti littering practices. Overall, this study contributes to the development of a more systematic behavior change based micro intervention framework for understanding and addressing littering behavior in both theoretical and practical terms.